DEVELOPING MIND MAPPING MODEL BASED ON PROPHETIC VALUES IN WRITING EXPOSITION TEXT - Neneng Maelasari; Dadang Sunendar; Andoyo Sastromiharjo; Yeti Mulyeti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research and development aimed to achieve 2 main objectives: to develop a mind mapping model based on prophetic values in writing exposition texts, and to describe and discuss the profile of mind mapping model based on prophetic values in writing exposition texts. This model was developed by using 4D model (definition, design, development, and dissemination) which was modified to 3DI (definition, design, development, and implementation). This research was conducted in the academic year 2019/2020 at a high school in Bandung. The instruments of this research were questionnaires and observation sheets that fulfilled the validity and reliability requirements. The initial product was tested on a limited trial in X IPA SMA Negeri 1 Baleendah Bandung. Then, the revised product was tested extensively in 2 classes, namely X IPA-3 and X IPS-5. The last procedure in this research was the dissemination of the final product prototype, which was teaching materials entitled Mind Mapping Based on Porphetic Values: Teaching Materials for Writing Exposition Texts for Grade X SMA/MA. This teaching material consisted of 30 pages, A4, time new roman, 12 automatic spaces outside the start page of 7. Ho was rejected for the paired sample t test because the sig. 0.037 < p = 0.05 for class X IPA-3 and the sig. 0.037 < p = 0.05 for class X IPS-5. This product was believed to contribute to the process of learning writing exposition texts at high schools. After that, as users, the Indonesian teachers scored in mode 4 for a scale of 1 to 4 for the 4 feasibility indicators. The score mode of 4 also occured in the assessment given by the expert team.